Accuracy of ultrasonography in the diagnosis of peritonitis compared with the clinical impression of the surgeon. - Kumar, Manesh (2002)
ABSTRACT: This prospective study has been conducted on thirty five nonconsecutive The peritonitis is a common acute surgical condition of the abdomen. Early diagnosis and proper treatment is essential to prevent morbidity and mortality. patients admitted to surgical ward through emergency and surgical outdoor patients department with clinical and ultrasonographic diagnosis and all the patients underwent laparotomy. All the patients showed features of peritomitis, out of which 46% patients were correctly diagnosed on the basis of history and clinical examination. All the patients were diagnosed ultrasongraphicallly also, out of which 86% of the patients got positive ultrasonographic findings against 14% normal ultrasonographic findings. The ultrasonographic findings were proved to be correct only in 13% cases as a result of laparatomy while in 87% of case the ultrasonographic findings proved to be incorrect. Thus clinical diagnostic findings have been proved to be more accurate than ultrasonographic diagnosis of peritonitis. Therefore, the present study concludes that clinical diagnosis based on history and clinical examination is significantly superior to the Ultrasonography and it is not necessary to be performed in case of clinically diagnosed peritounitis.